ANALISIS PELAYANAN PERIZINAN TENAGA KESEHATAN DENGAN APLIKASI SISTEM INFORMASI CERDAS LAYANAN TERPADU UNTUK PUBLIK (SICANTIK) DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN WONOGIRI - Artika Mukti Barokah; Endang Larasati Setianingsih; Dyah Lituhayu (Journal of Public Policy and Management Review, 2023)
This study aims to analyze the quality of health worker licensing services with the application of an integrated service intelligent information system for the public (SICANTIK) at DPMPTSP Wonogiri Regency as well as identify and analyze the driving and inhibiting factors of service quality using service quality theory according to Zeithaml, Parasuraman and Berry with the help of data analysis in the form of software Atlas.ti. The results indicate which the quality of health worker licensing services is still not optimal in the dimensions of tangible, reliability and responsiveness. The problems found include unfulfilled facilities, inaccuracy in the timing of license issuance, lack of ability and accuracy of employees, slow response and rejection of applicant data. The inhibiting factors are network disruptions and errors in the SICANTIK application system, maintenance, limited competence of implementing resources in the IT field and not optimal communication and socialization. The recommendation is a priority scale can be determined in developing facilities and infrastructure and providing supporting facilities, conducting training and increasing employee capacity regarding the use of the SICANTIK application system and conducting socialization effectively and on target